The interface between the sacrificial rites in yoruba religion and African indigenous churches (2020)
The idea of sacrifice which by definition has remained multi-dimensional and generalised has continued to be an attractive concept in religious and theological discourse. The reason is that sacrifice seems to connote different meanings to different people, especially adherents of different religions. Even in the same religion such as Christianity for instance, people express divergent understanding of the concept. To some groups of Christians, the suffering and death of Jesus Christ epitomise the sacrifice sufficient for all generations. But some Christian denominations share the view of African Religions, which is similar to Judaist religion on sacrifice as a daily and practical offering of food, objects or the lives of animals to God, the ancestors or spirits for the purpose of achieving individual or general well- being of the society. This paper therefore seeks to bring to the fore some sacrificial practices among the African Indigenous Churches which have resemblance in Yoruba religion with a view to determining the validity of such practices within the biblical context and the history of African Christianity.